ANALISA PRODUKTIVITAS DAN PENDAPATAN USAHA TANI PADI SAWAH DIDESA LAWANG AGUNG KECAMATAN KEDURANG KABUPATEN BENGKULU SELATAN - sumantri, Bambang; Fauzi, Emlan (Jurnal AGRISEP, 2006)
This reseach is intended  to find out the prodictivfty  level, farm income and the factors influenced productivity  of  wetland paddy  farm.  This reseach  was conducted  at viI/age Lawang  Agung sub-district Kedurang district South Bengkulu on july  and august 2005. stratified random sampling methode was used to select 62 responden.   The analysis  use  are  farm productivity, income analysis  and  Cobb Douglas production  function. The result show that  average productivfty  of wetland paddy  is 2620,97 kg/ha,  while average income is Rp. 1.207.308, 91111aT. he result also show that factors that influenced productivfty level are seed, urea fertilizer,  the distance  of farm area of to the water intake  and rented land basis of land utilazation.  While KCI fertilizer, SP-36 fertilizer,pesticide.labor,  owned land basis of  land utilalazation, and share crops basis of land utilalazation  were not significant.